Analisis Konsep Pesawat Sederhana Pada Pembelajaran Ilmu Pengetahuan Alam Berbasis Tradisi Sains Islam Di Madrasah Tsanawiyah - Zakwandi, Rizki (BELAJEA: Jurnal Pendidikan Islam, 2017)
Abstract: Science learning in Islamic school is too less that orientation to Muslim scientist discoveries. Mainly, the theory that teaching to the student is adapted by the Westrn scientist discoveries. The study aim to rebuild treasure of the science in Muslim community throught learning orientation by the Muslim scientist discoveries, so that student would be more familiar with Muslim scientist and literating to work and glory of the Islam as before. The mehtod used in this project is the qualitative methode in the Islamic scientifict tradition approach and case study in the learning science books at the Islamic school. The result of research conduction show that there are similarity of principle by Physics modern scientist and Thabit ibn Qurra about the simple machine. Case study conduction show that only 13,51% textbooks are used at the Islamic School that giving information about Muslim scientist and their work by 75,67% textbooks that giving information about scientist. The solution offered to solve the problem is to make a textbook or handbook with largely contans the knowledge of the Muslim scientist. Keywords: Simple machine, Islamic scientifict tradition, Muslim scientist, Physic